Long-term prognosis of patients undergoing radiofrequency catheter ablation for atrial fibrillation: comparison between heart failure subtypes based on left ventricular ejection fraction. Issue 4 (31st August 2021) - Fujimoto, Hajime; Doi, Naofumi; Okayama, Satoshi; Naito, Masaki; Kobori, Atsushi; Kaitani, Kazuaki; Inoue, Koichi; Kurotobi, Toshiya; Morishima, Itsuro; Yamaji, Hirosuke; Matsui, Yumie; Nakazawa, Yuko; et al.
Abstract: Aims: Heart failure (HF) prognosis has been reported similar in patients with preserved vs. reduced left ventricular ejection fraction (LVEF). This study compared the long-term prognosis of HF patients undergoing radiofrequency catheter ablation (RFCA) for atrial fibrillation (AF). Methods and results: Among 5010 patients undergoing RFCA in Kansai Plus AF registry, 656 patients (13.1%) with a documented history of HF were enrolled in the study before RFCA. The primary endpoint was a composite of all-cause death, HF hospitalization, and stroke or systemic embolism. Patients with reduced (<40%), mid-range (40–49%), and preserved (≥50%) LVEF were 98 (14.9%), 107 (16.3%), and 451 (68.8%) patients, respectively. The prevalence of ischaemic heart disease and cardiomyopathies was higher among patients with reduced as compared with preserved LVEF (27.6% vs. 10.0%, P  <   0.05 and 36.7% vs. 15.3%, P  <   0.05, respectively). The median follow-up period was 2.9 years. The 3-year cumulative risk for the primary endpoint was higher in patients with reduced LVEF (32.7%) compared to those with mid-range (11.7%) or preserved (11.6%) LVEF ( P  <   0.001). Reduced LVEF was the most significant independent risk factor for primary endpoint (hazard ratio, 2.83; 95% confidence interval 1.74–4.61, P  <   0.001). The 3-year arrhythmia recurrence rate was similar among the groups (48.2%, 42.8%, and 47.3%, respectively, P  =   0.75). Conclusion : This study raises hypothesis that patients with HFrEF and AF had approximately three times higher risk for a composite of all-cause death, HF hospitalization, and stroke or systemic embolism after AF ablation compared with patients with HFmrEF or HFpEF.